A new framework for understanding stress and disease: the developmental model of stress as applied to multiple sclerosis - Fauver, Michelle; Clark, Eva M.; Schwartz, Carolyn E. (Frontiers in Integrative Neuroscience, 2024)
This paper proposes a new model of stress that integrates earlier models and adds insights from developmental psychology. Previous models describe the behavioral and physical effects of stress events, but have not explained the translation of experiences into stress itself. The Developmental Model of Stress shows how psychosocial developmental challenges in childhood create persistent negative beliefs and behaviors that increase threat perception and maladaptive stress responses. These developmental challenges produce early psychological and physiological predispositions for increased stress responses over time. Ongoing stress leads to dysregulation of physical stress-response systems (allostatic load), which is associated with multiple diseases. High allostatic load provides the necessary preconditions for the diathesis-stress model, which says the addition of an acute stressor to a weakened or predisposed system can lead to disease development. The paper also documents the evolving measurement of stress to better understand the stress-disease relationship, helping to resolve conflicting results between studies. The Developmental Model of Stress was combined with clinician insight and patient reports to build an integrative framework for understanding the role of stress in the development and progression of multiple sclerosis (MS). It includes the first mapping of maladaptive beliefs and behaviors arising from developmental challenges that are common to people with MS. An initial comparison shows these may be distinct from those of people with other chronic diseases. These beliefs and behaviors form the predisposing factors and contribute to the triggering factors, which are the acute stressors triggering disease onset. These often took two forms, a prolonged incident experienced as feeling trapped or stuck, and threat of a breach in a relationship. The reinforcing factors add the stress of a chronic disease with a poor prognosis and seemingly random symptom fluctuation, still managed with the same beliefs and behaviors developed in childhood, increasing physiological dysregulation and symptom severity. A pilot study is described in which these three categories of stress factors in MS were explicitly addressed. This study noted clinically important improvements in physical and mental well-being, providing preliminary support for the Developmental Model. Future research might expand on the pilot using a more robust sample and design.